Photoluminescence quenchers in drug discovery - Vuorinen, Emmiliisa (fi=Turun yliopisto|en=University of Turku|, 2021)
During the drug discovery process molecular libraries containing millions of molecules are screened to find a single potential drug with the highest potency and efficacy over unwanted side-effects. The whole drug development process usually takes more than a decade and requires billions of euros. Thus, new methods with improved cost and time effectiveness are vital for both improving primary screening of molecular libraries and verifying the results obtained via secondary screens. Drug discovery often utilizes methods based on photoluminescence, the emission of light from a luminophore molecule excited by photon absorption, e.g. fluorescence. The methods monitor changes in photoluminescence that are initiated by an event in the assay e.g. interaction of protein and ligand. In some methods, the detectability of the change can be enhanced by decreasing the luminescence of noninteracting luminophores by quenching. Some luminophores are quenched by water but others require dedicated quencher molecules e.g. the acceptor molecules quenching donor luminophores in Förster resonance energy transfer (FRET). In the work presented in this thesis, the addition of a soluble quencher was utilized for developing two photoluminescence-based assays suitable for drug discovery for studying protein-ligand interactions (PLI), protein-protein interactions (PPI), and protease activity. The first method developed, QTR-FRET, utilizes soluble quencher to decrease the emission of non-interacting donor luminophore thus preventing it from interfering in the monitored acceptor channel. QTR-FRET improves conventional TR-FRET by permitting the investigation of low affinity PLI interactions requiring high donor luminophore concentrations and by enabling multiplexing via monitoring PLI and subsequent PPI. The second method, the Protein-Probe, was developed to measure the emission of external luminescence probe during its interaction with a target protein. The emission of non-interacting probe is reduced by soluble quencher. The Protein-Probe is suitable for monitoring the PLIs via their effect on the thermal stability of protein and the protease activity via the digested protein substrate. The Protein-Probe has 50-fold improved sensitivity compared to conventional methods.

Loistevalon sammuttajat lääkekehityksessä Varhaisen lääkekehityksen aikana miljoonia molekyylejä sisältävistä molekyylikirjastoista seulotaan lääkemolekyyli, joka vaikuttaa sairauteen mahdollisimman tehokkaasti välttäen haitallisia sivuvaikutuksia. Yleensä lääkekehitysprosessi kestää yli vuosikymmenen ja kuluttaa miljardeja euroja. Tämän vuoksi uusia aika- ja kustannustehokkaita menetelmiä tarvitaan parantamaan ensisijaista seulontaa sekä varmistamaan niiden tulokset toissijaisella seulonnalla. Varhaisessa lääkekehityksessä hyödynnetään usein menetelmiä, jotka perustuvat fotoluminesenssiin, eli valon tuotantoon luminofori molekyylistä, joka on virittynyt fotonin imeytymisen vuoksi, kuten fluoresenssiin. Menetelmät tarkkailevat luminesenssiin vaihtelua, minkä saa aikaan tapahtuma määrityksessä kuten proteiinin ja ligandin vuorovaikutus. Joissain menetelmissä tapahtuman havaitsemista voidaan tehostaa sammuttamalla sitoutumattomien luminoforien luminesenssia. Jotkut luminoforit voidaan sammuttaa vedellä, mutta toiset vaativat erillisen molekyylin kuten Förster resonanssi energiasiirron (FRET) luovuttaja luminoforeja sammuttavat vastaanottaja molekyylit. Tässä väitöskirjassa liukoisen sammuttajan lisäystä käytettiin kehittämään kaksi lääkekehitykseen soveltuvaa fotoluminesenssimenetelmää, jotka tarkkailevat proteiini-ligandi (PLV), proteiini-proteiini vuorovaikutuksia sekä proteaasien aktiivisuutta. Ensimmäiseksi kehitetyssä QTR-FRET menetelmässä sammuttajaa käytetään vähentämään sitoutumattomien luovuttaja-luminoforien valon tuotantoa, jolloin niiden aiheuttama häiriö vastaanottajamolekyylin luminesenssia mitattaessa vähenee. QTR-FRET mahdollistaa korkeaa luovuttajapitoisuutta tarvitsevien matalan affiniteetin PLV:en sekä kahden linkittyneen vuorovaikutuksen tarkkailun yhteisestä kaivosta. Toinen kehitetty menetelmä, Protein-Probe, mittaa erillisen koettimen luminesenssia sen sitoutuessa proteiiniin. Sitoutumattoman koettimen luminesenssi himmentyy liukoisen sammuttajan vaikutuksesta. Protein-Probella voi tarkkailla PLV:ia proteiinien lämpöpysyvyyden välityksellä, sekä proteaasien aktiivisuutta niiden hajottamien substraattiproteiinien kautta. Protein-Probe menetelmän herkkyys on 50-kertainen verrattuna vastaaviin menetelmiin.